Comparison of the influence of influencer marketing and affiliate marketing on digital consumer purchasing decisions - Wilda Tul Uluf; Abdullah Yaqin; Zainur Ridho; Mohammad Muzaki; Mokhamad Yaurizqika Hadi (Alkasb: Journal of Islamic Economics, 2025)
This research conducts a comparative analysis of how influencer marketing and affiliate marketing impact digital consumer purchasing behavior in today's social media-dominated landscape. As digital technologies advance and social media usage grows exponentially, businesses are increasingly adopting these platform-based marketing approaches to engage target audiences. Employing qualitative methodology through systematic literature review (SLR), the study examines secondary data from academic publications and relevant sources. Findings reveal that influencer marketing demonstrates greater effectiveness in establishing consumer trust and emotional connections, leveraging influencers' perceived credibility and personal rapport with their audience. Conversely, affiliate marketing proves more efficient in driving direct conversions while maintaining cost-effectiveness through its incentive-based structure. Each approach offers distinct advantages that can be strategically deployed based on specific market segments and product characteristics. The study emphasizes the need for flexible, integrated digital marketing strategies, proposing synergistic implementation of both methods. These insights equip businesses with valuable guidance for formulating marketing policies that harness the complementary strengths of both strategies to enhance competitiveness in the global digital marketplace.